Domino: Understanding Wide-Area, Asynchronous Event Causality in Web Applications - Li, Ding; Mickens, James; Nath, Suman; Ravindranath, Lenin (ACM Symposium on Cloud Computing conference (SOCC), 2015)
In a modern web application, a single high-level action like a mouse click triggers a flurry of asynchronous events on the client browser and remote web servers. We introduce Domino, a new tool which automatically captures and analyzes end-to-end, asynchronous causal relationship of events that span clients and servers. Using Domino, we found uncharacteristically long event chains in Bing Maps, discovered data races in the WinJS implementation of promises, and developed a new server-side scheduling algorithm for reducing the tail latency of server responses.